On Research for Tourism Management - Sthapit, Arhan (PYC Nepal Journal of Management, 2012)
Book review Nepal Tourism & Development Review; Nepal Tourism Board (NTB) and Kathmandu University School of Arts; Volume 1, Issue 1; Kathmandu: 2011; Pages: 130+4; Price: Not mentioned.